Clinical and Imaging Findings of Musculoskeletal Melioidosis in the Right Hip: A Case Report - Myung Hyun Kim; Tong Jin Chun (대한영상의학회지, 2018)
Melioidosis is an infectious disease caused by a Gram-negative bacterium thought to be caused Burkholderia pseudomallei. This disease is endemic in tropical regions, but is not endemic and is rarely encountered in Korea. Nevertheless, the importance of early diagnosis of melioidosis is drawing substantial attention, due to its proliferation and the high mortality caused by the disease. Melioidosis can attack any organ, and manifests with a variety of symptoms. In particular, musculoskeletal melioidosis is rare and presents with nonspecific musculoskeletal symptoms. The imaging features of musculoskeletal melioidosis manifest a form of osteomyelitis or septic arthritis with soft tissue abscess or can mimic a bone tumor. This study describes the clinical and imaging findings of melioidosis involving the right femur and hip joint in a 64-year-old man.